PCSK9 Inhibitor: Safe Alternative to Fill the Treatment Gap in Statin-Limited Conditions? - Ying Xiao; Zhengqing Ba; Shurui Pang; Dong Liu; Hao Wang; Hanyang Liang; Yong Wang; Jiansong Yuan (Reviews in Cardiovascular Medicine, 2022)
Lipid-lowering therapy is of great importance in reducing the burden of atherosclerotic cardiovascular disease. Statins act as first-line therapy in the current lipid management guidelines. However, statin use is limited in (1) statin-induced adverse events, including statin-associated muscle symptoms, new-onset diabetes mellitus, drug-induced liver injuries, acute kidney injuries, cognitive effects, hemorrhagic strokes, and cataracts; (2) special populations, including pregnant and lactating patients, patients with decompensated cirrhosis, and patients on dialysis; (3) coadministration with statin-interactive drugs, such as anti-human immunodeficiency virus drugs, anti-hepatitis C virus drugs, and immunosuppressive drugs. These considerable statin-limited groups are in urgent need of safer alternative lipid-lowering options. Proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibitors are attracting widespread attention for their documented safety in general populations and superior lipid-lowering properties. Therefore, questions have been raised whether PCSK9 inhibitors could be a safe alternative in patients who are intolerant to statin therapy. In this review, we discuss the safety of PCSK9 inhibitors in statin-limited conditions. We conclude that PCSK9 inhibitors are a safe alternative lipid-lowering therapy in various statin-limited conditions. Furthermore, we identify several limitations in the current literature and suggest future directions, for the refinement of lipid management regimens.